Mania associated with interferon α2b treatment - Basanth K (Journal of Postgraduate Medicine, 2006)
Neuropsychiatric side effects are common with Interferon α 2b. Psychosis and depression have been reported. Several cases of mania have been reported but only few have been associated with treatment for hepatitis B. We report a case of mania with psychotic symptoms in a 21-year-old female diagnosed to have hepatitis-B infection, who was receiving interferon. The report supports the view that dose reductions or pauses during interferon treatment can cause mania. Family history of mood disorder could be a risk factor. Atypical presentations are common in interferon-induced mania. Mania induced by interferon responds well to antimanic drugs. Since the use of interferon is increasing in developing countries, the need for awareness of side effects and management issues are important and these are highlighted.